Asteroid Observations with NCSFCT’s AZT-8 Telescope - Kozhukhov, O.M.; Maigurova, N.V. (Science and Innovation, 2024)
The asteroid observations of the small Solar System bodies were carried out with the AZT-8 telescope (D=0.7 m, f/4) of the National Center of Space Facilities Control and Testing (NCSFCT) during 2010-2013. The telescope is located near Yevpatoria, the observatory code according IAU is B17. The observational program included perturbed main belt asteroids and NEO’s for the GAIA FUN-SSO Company. The MPC database contains more than 4500 asteroids positions and magnitudes obtained during this period at AZT-8 telescope. The article presents analysis of the positional accuracy of B17 observations obtained from the comparison with the JPL HORIZONS ephemeris, and data from AstDyS-2 and NEODyS-2 web services.